Psoriatic Synovitis: Singularity and Potential Clinical Implications - Celis, Raquel; Cuervo, Andrea; Ramírez, Julio; Cañete, Juan D. (Frontiers in Medicine, 2019)
Psoriatic arthritis (PsA) is an immuno-inflammatory disease with a heterogeneous clinical presentation as affects musculoskeletal tissues (arthritis, enthesitis, spondylitis), skin (psoriasis) and, less frequently, eye (uveitis) and bowel (inflammatory bowel disease). It has been suggested that distinct affected tissues could exhibit different immune-inflammatory pathways so complicating the understanding of the physiopathology of psoriatic disease as well as its treatment. Despite of the key pathogenic and clinical relevance that enthesitis has in PsA, peripheral arthritis is more easily perceived. At the macroscopic level, PsA synovitis has predominantly tortuous, bushy vessels, whereas rheumatoid arthritis (RA) is characterized by mainly straight, branching vessels so reflecting prominent neo-angiogenesis in PsA. Synovial biopsies have demonstrated a similar cellular and molecular picture in PsA and RA, although some differences have been reported at the group level, as higher density of vessels, CD163+ macrophages, neutrophils and mast cells in PsA. In fact, synovial IL-17+ mast cells are significantly increased in PsA and produce more IL-17A compared with RA, and a proof of concept study supports its relevant role in the synovitis of SpA, included PsA. As firstly reported in RA, synovial lymphoid neogenesis is found also in the same proportion of PsA as in RA patients, despite the lack of autoantibodies in PsA. These lymphoid structures are associated with activation of the IL-23/Th17 pathway in RA and seemly in PsA, which could be useful to stratify RA patients. Immunohistochemical and transcriptomic methodologies have still not found synovial biomarkers useful to distinguish psoriatic from rheumatoid synovitis at the patient level. However, modern methodologies, as MALDI-Mass Spectrometry Imaging, applied to the study of synovial tissue have revealed metabolic and lipid signatures which could support clinical decision-making in the diagnosis of PsA and RA and to go further towards the personalized medicine. Key words: psoriatic arthritis, rheumatoid arthritis, synovitis, cellular infiltrate, histology, immunohistochemistry, macrophage-polarization, microarrays, mass spectrometry image, metabolome.